Tae-miR396b regulates TaGRFs in spikes of three wheat spike mutants - Ziping Yao; Qi Wang; Ying Xue; Zhiheng Liang; Yongjing Ni; Yumei Jiang; Peipei Zhang; Ting Wang; Qiaoyun Li; Lei Li; Jishan Niu (PeerJ)
Tillering and spike differentiation are key agronomic traits for wheat (Triticum aestivum L.) production. Numerous studies have shown that miR396 and growth-regulating factor genes (GRFs) are involved in growth and development of different plant organs. Previously, we have reported that wheat miR396b (tae-miR396b) and their targets TaGRFs (T. aestivum GRFs) play important roles in regulating wheat tillering. This study was to investigate the regulatory roles of tae-miR396b and TaGRFs played during wheat spike development. Wheat cultivar Guomai 301 (wild type, WT) and its three sipke mutants dwarf round spike mutant (drs), apical spikelet sterility mutant (ass) and prematurely terminated spike differentiation mutant (ptsd1) were studied. Three homeologous genes of tae-miR396b on the long arms of chromosomes 6A, 6B, and 6D were identified, and they encoded the same mature miRNA. Complementary sequences of mature tae-miR396b were identified in 23 TaGRFs, indicating they were the target genes of tae-miR396b. Tae-miR396b had different regulatory effects on TaGRFs between Guomai 301 and its mutants. TaGRF2-7A was confirmed to be the target gene of tae-miR396b by molecular interaction assay. The expression levels of tae-miR396b and TaGRFs were different between WT and mutants drs, ass and ptsd1 at the floret primordium visible (S1), the two awns/spikelet reaching apical meristem of the spikelet (S2), and the green anther stage (S3). The expression level of tae-miR396b in WT was significantly higher than that in mutants drs and ass. The most TaGRFs were negatively regulated by tae-miR396b. The abnormal expressions of TaGRF1 (6A, 6D), TaGRF2 (7A, 7B, 7D), TaGRF4 (6A, 6B), TaGRF5 (4A, 7A, 7D), and TaGRF10 (6A, 6B, 6D) were important causes for abnormal spike development in the three mutants. This study laid foundation for further elucidating functions of tae-miR396b and TaGRFs underlying wheat spike development. Regulating tae-miR396b and TaGRFs will be a new approach for wheat high yield breeding.